PERENCANAAN BANGUNAN PELINDUNG PANTAI TAMBAKHARJO, SEMARANG - candrawati Mareta Prawarti; Wahyu Setia Prihardhani; Dwi Kurniani; Priyo Nugroho P. (Jurnal Karya Teknik Sipil, 2013)
Tambakharjo coast located in Semarang. Tambakharjo coast damaged a shoreline setback. Construction of coastal protection building a seawall is one way to prevent more serious damage to the coast. Construction of coastal protection building is expected to maintain the shoreline. Analysis of wind data, tidal data, and soil data is needed to determine height and period of waves, sea level value, and the carrying capacity of the soil in the planning of coastal structures. Besides that, flow analysis using model ADCIRC in program SMS (Surface-water Modelling System) and forecasting changes of shoreline with program GENESIS (Generalized Model for Simulating Shoreline Change) is used to specify an alternative coastal structures within the next few years. Selection of coastal structures using the Analysis Hierarchy Process (AHP). Based on the AHP scoring system obtained the highest priority value that is coastal structure with seawall construction. Seawall construction is planned along the Tambakharjo coast 1200 and with a Mercu elevation  3 meters to reduce the creeping wave.